2013
DOI: 10.21109/kesmas.v7i7.27
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Perilaku Pemberian Air Susu Ibu Eksklusif pada Ibu Pekerja

Abstract: 298 AbstrakPemerintah Indonesia menargetkan cakupan pemberian air susu ibu (ASI) eksklusif sekitar 80%, tetapi hasil Riset Kesehatan Dasar tahun 2010 menunjukkan cakupan ASI eksklusif baru mencapai 15,3%. Dari tahun ke tahun, prevalensi pemberian ASI eksklusif cenderung menurun dengan berbagai alasan, antara lain ibu pekerja. Penelitian ini bertujuan untuk mengetahui proporsi pemberian ASI eksklusif pada ibu pekerja. Rancangan penelitian yang dipakai adalah potong lintang pada data primer yang terdiri dari 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 4 publications
2
19
1
9
Order By: Relevance
“…The results showed there was no correlation between workplace facilities with exclusive breastfeeding (p> 0.05). This study is not consistent with Abdullah (2013), research that found a correlation between the availability of facilities with exclusive breastfeeding.…”
Section: Methodscontrasting
confidence: 99%
See 1 more Smart Citation
“…The results showed there was no correlation between workplace facilities with exclusive breastfeeding (p> 0.05). This study is not consistent with Abdullah (2013), research that found a correlation between the availability of facilities with exclusive breastfeeding.…”
Section: Methodscontrasting
confidence: 99%
“…As health workers, they should have a good knowledge of being a mother, because people generally get the information about health, especially exclusive breastfeeding from health workers. This finding is supported by Abdullah (2013), in which the mothers who worked as health workers both medical and non-medical are have more knowledge than mothers who do not work. The research shows there is no correlation between having knowledge with exclusive breastfeeding (p> 0.05).…”
Section: Methodsmentioning
confidence: 72%
“…This variable was categorized into 'low expossure' if the mother get exposure of exclusive breastfeding less than three times per week from one source of information, and 'high expossure' if the mother got exposure to exclusive breastfeeding greater than or equal than three times per week at least from one source of information exposure. 26 Exposure to exclusive breastfeeding from social media was the exposure of mother to information about exclusive breastfeeding from social media (BBM/facebook /twitter/whatsapp/instagram/others). 17 This variable was categorized into low exposure if the mother obtained information on exclusive breastfeeding not everyday from one social media source, and high exposure if the mother got information on exclusive breastfeeding every day at least from one social media source.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies in Indonesia have suggested that apart of knowledge capacity building, a lactation counselor at work, lactation facilities, and support by peers would be critical and hence could help working mothers continue breastfeeding and have a positive breastfeeding attitude. [21][22][23] Family support also plays an important role. 6 These factors are key to potentially help mothers to have positive attitude of breastfeeding despite the lower and inadequacy knowledge of breastfeeding.…”
Section: Relationship Between Breastfeeding Knowledge and Attitude Ammentioning
confidence: 99%